Pengaruh Komunikasi Antarpersonal Terhadap Etos Kerja Pegawai (Studi Pada Kantor Sekretariat Daerah Kota Kendari) - Surianingsih, Made; Utha, Arifin; Liwaul, Liwaul (Universitas Halu Oleo, 2020)
The purpose of this study was to determine the effect of interpersonal communication on the work ethic of employees at the Kendari City Regional Secretariat Office. The population in this study were 498 employees at the Regional Secretariat Office of Kendari City. The sample in this study was determined by proportional random sampling with a sample size of 84 respondents. The method used in this research is descriptive quantitative. The results in this study indicate that interpersonal communication consists of dimensions of 1) openness, 2) empathy, 3) support, 4) positivity, 5) equality, which have a significant effect on work ethic. Then based on the results of the analysis of the influence of interpersonal communication on the work ethic of employees at the Regional Secretariat Office of Kendari City, it shows that the effect of interpersonal communication is 45,8% and the remaining 54,2% is caused by other factors. Then the dimension of interpersonal communication at the Kendari City Regional Secretariat Office which gives the highest reflection to the work ethic of employees is the dimension of quality. Meanwhile, the dimension of interpersonal communication at the Kendari City Regional Secretariat Office which gives the lowest reflection to the work ethic of employees is the dimension of openness.